A composite score to assess the burden of periodontal diseases and tooth loss. Issue 10 (1st July 2019) - Lamster, Ira B.; Cheng, Bin; Liao, Ziwei; Shearer, Barbara
Abstract: Background: Population studies of the prevalence of oral disease rely upon indices that summarize disease status. There is no universally accepted index that summarizes the burden of periodontal diseases, considering the number of teeth remaining in the mouth. Methods: A new conceptual index was developed that includes consideration of the extent and severity of the periodontal diseases, the distribution of affected teeth, and tooth loss as a function of age. The index is referred to as the burden of periodontal diseases and tooth loss (BPT). Results: A cohort of 1, 097 individuals originally seen as new patients in a dental school clinic, and evaluated for undiagnosed dysglycemia, were studied. The BPT index was applied to this data set. A modifying effect of considering the number of lost teeth was observed. The distribution of scores w skewed to the left, which gradually shifted to the right when the most involved teeth (periodontal pathology, tooth loss) were weighted more heavily. This shift was not observed when missing teeth were not considered. Conclusions: This conceptual study illustrates that the extent and severity of periodontal pathology, and number and distribution of missing teeth, are important considerations when summarizing the condition of the mouth. The BPT provides a measure of the oral disease burden, as both periodontal pathology and tooth loss are associated with both functional impairment and reduced quality of life. The dental profession and dental research community must continually seek to develop new approaches to defining and summarizing the oral disease burden.